Gamification: An Approach in Developing Social Skills of Kindergarten Learners - Argueza, Lyka Abegail (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed gamification as an approach in developing the social skills of kindergarten learners in public elementary schools of Naguilian District, Division of La Union, during the school year 2025–2026. Guided by relevant learning theories and an Input-Process-Output framework, the study examined the perceived importance of gamification, the effectiveness of gamified strategies, the manifestation of learners’ social skills, the extent of gamification’s effects, problems encountered in implementation, and the differences between the perceptions of kindergarten teachers and school administrators. The study used a descriptive research design and a validated researcher-made questionnaire administered to thirty-five kindergarten teachers and twenty-seven school administrators, with data analyzed using frequency counts, weighted means, rankings, and t-test. Findings showed that both groups perceived gamification as highly important, the strategies as highly effective, learners’ social skills as highly manifested, and the effects of gamification as great in extent. Gamification was especially associated with active participation, cooperative learning, teamwork, joyful play, storytelling, relays, and body language activities. However, problems such as large class size, learners’ difficulty in following instructions, lack of discipline, and noisy classroom conditions were rated moderately serious. Significant differences were found in perceptions of the importance and effect of gamification, while no significant differences were found in strategy effectiveness, social skill manifestation, and problems encountered. The study concluded that gamification is necessary, relevant, and influential in developing kindergarten learners’ social skills. It recommended the adoption of intervention strategies to strengthen weaker areas such as sportsmanship, camaraderie, respect for others’ rights, and help-seeking behaviors. The study supports SDG 4, SDG 3, SDG 10, and SDG 17 by promoting inclusive early childhood learning, socio-emotional well-being, adaptable participation, and stakeholder collaboration. Its sustainability impact lies in supporting educational, socio-emotional, institutional, and community development through improved classroom engagement, teacher practice, and child social competence.
Keywords: Adaptability; Classroom Management; Early Childhood Education; Gamification; Kindergarten Learners; Naguilian District; Social Skills; Teamwork